SEEING THE MULTICULTURALISM THROUGH VARIOUS INDONESIAN FOLKTALES - Muhammad Rifqi (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2011)
Indonesia lies between Asia and Australia continents. It hasapproximately 17,508 islands that make it one of the largest archipelagos in the world spanned from Sabang (in Aceh, Sumatra Island) to Merauke (in Papua Island). The considerable number of its islands is inhabited by numerous ethnic groups that also bring about various cultural arts. Indonesia is famous for its multiculturalism as well. This paper tries to investigate the perspectives of landscape of nature through the languageexpressions in various Indonesian folktales by using the structuralapproach. It is an attempt to disclose the visual imageries reflected in the folktales to know the varieties of Indonesian cultures. The data were taken from several folktales owned by some ethnic groups in Indonesia which were anonymously created and told from generation to generation. The findings showed the variety of unique visions and perspectives about landscape among the ethnic groups reflected through the imageries in the language of each folktale.Keywords: ethnic group, folktale, Indonesia, landscape, language,multiculturalism,